Defense Mechanisms of Elementary School Children in Dealing with Emotional Stress (A Freudian Psychoanalytic Perspective) - Muhdiati, Siti; Riyadi, Arie Rakhmat (International Conference on Elementary Education, 2025)
Emotional pressure in elementary school children is an important issue that can significantly affect their psychological development. Defense mechanisms, from Freud’s psychoanalytic perspective, function as unconscious strategies to cope with such pressure. This quantitative study aims to analyze the defense mechanisms used by fifth-grade students in West Bandung Regency to deal with emotional stress. A total of 66 students were selected through purposive sampling, and data were collected using a structured questionnaire measuring four types of defense mechanisms: denial, sublimation, reaction formation, and projection. Data were analyzed using descriptive and inferential statistics (Kruskal–Wallis test). The results revealed that sublimation had the highest mean score (M = 2.89; SD = 0.787) and was the most dominant strategy used by students to manage emotional pressure, followed by denial (M = 2.27) and reaction formation (M = 2.26), while projection was the least used mechanism (M = 1.64). The Kruskal–Wallis test yielded H = 70.875; p < 0.001, indicating a significant difference among the four types of defense mechanisms. Post hoc analysis with Bonferroni correction confirmed that sublimation differed significantly from other mechanisms, while denial and reaction formation were used at relatively similar levels. These findings indicate that elementary school children tend to employ adaptive defense mechanisms when facing emotional pressure. The results are expected to serve as a foundation for developing psychological interventions in schools, including emotional regulation training and positive coping strategies to enhance children’s emotional well-being.